Preparation method and application of nano additive material composite powder

By combining Al powder and Ni powder with nano-enhanced modified particles and ball agents, nano-additive material composite powder was prepared, which solved the problem of inconsistent performance of existing nano-additive products, and achieved coordinated improvements in mechanical properties, wear resistance and elongation, as well as improved stability of impact and cold and heat change.

CN119839315AActive Publication Date: 2025-04-18ZHONGKE BAOLU NEW MATERIALS (LIAONING) CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510329689.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-20
Publication Date
2025-04-18
Estimated Expiration
2045-03-20

AI Technical Summary

Technical Problem

Existing nanoadditive products have poor performance in terms of mechanical strength, wear resistance, elongation, impact resistance, and cold and heat resistance, making it difficult to achieve coordination of these properties.

Method used

Al powder and Ni powder are used as the main raw materials, nano-enhanced modified particles and ball mixing-based ball formulations are added, and nano-additive material composite powder is prepared through ball milling, selective laser melting and thermal improvement treatment.

Benefits of technology

The coordinated improvement of the mechanical properties, wear resistance and elongation of nano-additive materials is achieved, while improving the product's impact resistance and cold resistance stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of nano additive materials, in particular to a preparation method and application of nano additive material composite powder, and the preparation method comprises the following steps: weighing the following raw materials in parts by weight: 45-50 parts of Al powder, 5-7 parts of Ni powder, 8-12 parts of nano reinforced modified particles and 10-15 parts of a ball-milling-based ball preparation agent; according to the nano additive material composite powder, the Al powder and the Ni powder are matched, meanwhile, the added nano reinforced modified particles and the ball-milling-based ball-milling agent are blended and matched, and then ball-milling treatment, laser melting and final thermal improvement treatment are conducted, so that the mechanical property, the wear resistance and the ductility of the obtained nano additive material are improved in a coordinated mode; and meanwhile, the product is remarkable in impact resistance and cold and hot change resistance stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nano-additive materials, and in particular to a method for preparing a nano-additive material composite powder and an application thereof. Background Art

[0002] Additive manufacturing is a new manufacturing technology that integrates laser, precision transmission and CAD / CAM technologies. It uses fine laser focus spots to melt powder accumulation layer by layer to achieve additive manufacturing and realize the molding and manufacturing of metal parts of any complex shape. Existing nano-additive products have poor mechanical strength performance, low wear resistance and elongation. It is difficult for the product to achieve coordination of mechanical properties, wear resistance and elongation. At the same time, the product has poor impact resistance and resistance to cold and hot changes, which further limits the product's efficiency. Summary of the invention

[0003] In view of the defects of the prior art, the purpose of the present invention is to provide a method for preparing a nano-additive material composite powder and its application, so as to solve the problems raised in the above background technology.

[0004] The present invention solves the technical problem by adopting the following technical solution: The present invention provides a method for preparing a nano-additive material composite powder, comprising the following steps: Step 1: Weigh the raw materials by weight: 45-50 parts of Al powder, 5-7 parts of Ni powder, 8-12 parts of nano-enhanced modified particles and 10-15 parts of ball preparation based on ball milling; Step 2: feeding the above raw materials into a ball mill for wet ball milling, with a ball milling speed of 1000r / min and ball milling for 1h. After the ball milling is completed, filtering and drying are performed until the moisture content is less than 5%; Step 3: preparing additive material by selective laser melting the product of step 2; Step 4: The additive material is subjected to thermal improvement treatment, and finally ball-milled into powder, and then passed through 200 meshes to obtain nano-additive material composite powder.

[0005] Preferably, the energy density of the selective laser melting is 90 J / m, and the scanning speed is 1000 mm / s; and the selective laser melting method adopts plane line-by-line scanning and layer-by-layer scanning, and the energy density of each layer fluctuates by 20 J / m.

[0006] Preferably, the specific steps of the thermal improvement treatment are: first increase the temperature to 350°C at a rate of 2-5°C / min, keep warm for 2h, then reduce the temperature to 220°C at a rate of 3°C / min, keep warm for 1h, and finally air cool to room temperature.

[0007] Preferably, the preparation method of the nano-enhanced modified particles is: S01: Stir TiC in a sufficient amount of acid solution, then wash, filter and dry. Preheat the dried TiC powder at 55-60°C for 1h to obtain preheated TiC powder. S02: adding 3-5 parts by weight of cerium oxide and 1-3 parts by weight of silicon nitride to 5-8 parts by weight of 5% urea solution and mixing them thoroughly to obtain a first conditioning solution; 3-5 parts by weight of magnesium fluoride, 1-3 parts by weight of silane coupling agent KH550 and 4-7 parts by weight of sodium dodecyl sulfate solution are mixed to obtain a second conditioning solution; S03: the first conditioning liquid and the second conditioning liquid are stirred and mixed in a weight ratio of 3:5 to obtain a cerium-doped conditioning liquid; S04: subjecting the preheated TiC powder and the cerium-doped conditioning liquid to ultrasonic modification in a weight ratio of 4:7, and after the ultrasonic modification is completed, filtering and drying are performed to obtain a modified TiC agent; The conditioned TiC agent and the reinforcing agent were mixed and ball-milled in a weight ratio of 5:3 at a ball-milling speed of 1500 r / min for 2 h. After the ball-milling was completed, the particles were filtered and dried to obtain nano-enhanced modified particles.

[0008] Preferably, the acid solution is a sulfuric acid solution with a mass fraction of 5%; the mass fraction of the sodium dodecyl sulfate solution is 3-5%.

[0009] The nano-enhanced modified particles use TiC through acid solution and preheating treatment to optimize the activity efficiency of TiC, and then use cerium-doped conditioning liquid for ultrasonic improvement treatment. The first conditioning liquid and the second conditioning liquid in the cerium-doped conditioning liquid are mutually adjusted and improved. The first conditioning liquid is mixed with cerium oxide, silicon nitride and 5% by mass urea solution. The magnesium fluoride, silane coupling agent KH550 and sodium dodecyl sulfate solution in the second conditioning liquid are mixed and blended. Through the coordination and synergy between the raw materials, cerium oxide, silicon nitride and magnesium fluoride are blended into the TiC system, and then the conditioned TiC agent is further added to the product system, so that the performance of the product is further improved. The boron oxide, sodium silicate solution and nano-silica sol in the reinforcing agent are coordinated with each other, and then zirconium oxide and dopamine hydrochloride solution are blended and improved. Cobalt oxide is used to blend raw materials such as boron oxide, and the conditioned TiC agent is further matched, so that the performance coordination and performance stability of the product are further improved.

[0010] Preferably, the ultrasonic power of the ultrasonic modification treatment is 350-400W, and the ultrasonic treatment is performed for 20 minutes.

[0011] Preferably, the preparation method of the enhancer is: The boron oxide, sodium silicate solution and nano-silica sol are mixed and ball-milled in a weight ratio of (3-5): (7-11): 2, with a ball-milling speed of 1000 r / min for 2 hours, and the ball-milling is completed to obtain a compounding agent; 4-7 parts by weight of the compounding agent, 1-2 parts by weight of zirconium oxide and 5-8 parts by weight of dopamine hydrochloride solution are fully mixed to obtain a reinforcing agent.

[0012] Preferably, the mass fraction of the sodium silicate solution is 5-8%; the mass fraction of the dopamine hydrochloride solution is 2-5%.

[0013] By combining zirconium oxide with dopamine hydrochloride solution and a compounding agent, the compounding agent is improved by mixing boron oxide, sodium silicate solution and nano-silica sol. Through the coordinated optimization between the raw materials, the reinforcing agent is further enhanced and improved into the system, so that the performance of the product is further optimized and improved.

[0014] Preferably, the preparation method of the ball formulation based on ball milling is: S11: preparing a chitosan solution with a mass fraction of 3-5% and a sodium alginate solution with a mass fraction of 2-5%; S12: 3-5 parts of Ta powder are stirred in 5-8 parts of sodium alginate solution, and then 2-3 parts of chitosan solution and 1-2 parts of sodium carboxymethyl cellulose are added, and stirred in the second stage to obtain a ball preparation based on ball milling; wherein the stirring speed of the first stage stirring treatment is 550-600r / min, and the stirring is carried out for 15min; the stirring speed of the second stage stirring treatment is 300-350r / min, and the stirring is carried out for 40-50min.

[0015] The ball-milling-based ball additive is prepared by blending Ta powder with sodium alginate solution, chitosan solution and sodium carboxymethyl cellulose. Through the coordination between the raw materials, the ball-milling-based ball additive and the nano-reinforced modified particles are more effective. After the ball-milling-based ball additive is blended into the system, the interface improvement effect between the product raw materials is more obvious, thereby further improving the performance of the product.

[0016] The present invention also provides a method for preparing a nano-additive material composite powder and its application in laser melting additive manufacturing.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The nano-additive material composite powder of the present invention is prepared by combining Al powder and Ni powder, and nano-reinforced modified particles and ball additives based on ball milling are blended and coordinated, and then subjected to ball milling treatment, laser melting, and finally thermal improvement treatment. The mechanical properties, wear resistance and elongation of the obtained nano-additive material are improved in a coordinated manner, and the product has remarkable impact resistance and thermal stability. DETAILED DESCRIPTION

[0018] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] A method for preparing a nano-additive material composite powder of this embodiment includes the following steps: Step 1: Weigh the raw materials by weight: 45-50 parts of Al powder, 5-7 parts of Ni powder, 8-12 parts of nano-enhanced modified particles and 10-15 parts of ball preparation based on ball milling; Step 2: feeding the above raw materials into a ball mill for wet ball milling, with a ball milling speed of 1000r / min and ball milling for 1h. After the ball milling is completed, filtering and drying are performed until the moisture content is less than 5%; Step 3: preparing additive material by selective laser melting the product of step 2; Step 4: The additive material is subjected to thermal improvement treatment, and finally ball-milled into powder, and then passed through 200 meshes to obtain nano-additive material composite powder.

[0020] The energy density of the selective laser melting in this embodiment is 90 J / m, and the scanning speed is 1000 mm / s; and the selective laser melting method adopts plane line-by-line scanning and layer-by-layer scanning, and the energy density of each layer fluctuates by 20 J / m; The specific steps of thermal improvement treatment are: first increase the temperature to 350°C at a rate of 2-5°C / min, keep warm for 2 hours, then reduce the temperature to 220°C at a rate of 3°C / min, keep warm for 1 hour, and finally air cool to room temperature.

[0021] The preparation method of the nano-enhanced modified particles of this embodiment is: S01: Stir TiC in a sufficient amount of acid solution, then wash, filter and dry. Preheat the dried TiC powder at 55-60°C for 1h to obtain preheated TiC powder. S02: adding 3-5 parts by weight of cerium oxide and 1-3 parts by weight of silicon nitride to 5-8 parts by weight of 5% urea solution and mixing them thoroughly to obtain a first conditioning solution; 3-5 parts by weight of magnesium fluoride, 1-3 parts by weight of silane coupling agent KH550 and 4-7 parts by weight of sodium dodecyl sulfate solution are mixed to obtain a second conditioning solution; S03: the first conditioning liquid and the second conditioning liquid are stirred and mixed in a weight ratio of 3:5 to obtain a cerium-doped conditioning liquid; S04: subjecting the preheated TiC powder and the cerium-doped conditioning liquid to ultrasonic modification in a weight ratio of 4:7, and after the ultrasonic modification is completed, filtering and drying are performed to obtain a modified TiC agent; The conditioned TiC agent and the reinforcing agent were mixed and ball-milled in a weight ratio of 5:3 at a ball-milling speed of 1500 r / min for 2 h. After the ball-milling was completed, the particles were filtered and dried to obtain nano-enhanced modified particles.

[0022] The acid solution in this embodiment is a sulfuric acid solution with a mass fraction of 5%; the mass fraction of the sodium dodecyl sulfate solution is 3-5%.

[0023] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 350-400W, and the ultrasonic treatment is performed for 20 minutes.

[0024] The preparation method of the enhancer of this embodiment is: The boron oxide, sodium silicate solution and nano-silica sol are mixed and ball-milled in a weight ratio of (3-5): (7-11): 2, with a ball-milling speed of 1000 r / min for 2 hours, and the ball-milling is completed to obtain a compounding agent; 4-7 parts by weight of the compounding agent, 1-2 parts by weight of zirconium oxide and 5-8 parts by weight of dopamine hydrochloride solution are fully mixed to obtain a reinforcing agent.

[0025] The mass fraction of the sodium silicate solution in this embodiment is 5-8%; the mass fraction of the dopamine hydrochloride solution is 2-5%.

[0026] The preparation method of the ball preparation based on ball milling of this embodiment is: S11: preparing a chitosan solution with a mass fraction of 3-5% and a sodium alginate solution with a mass fraction of 2-5%; S12: 3-5 parts of Ta powder are stirred in 5-8 parts of sodium alginate solution, and then 2-3 parts of chitosan solution and 1-2 parts of sodium carboxymethyl cellulose are added, and stirred in the second stage to obtain a ball formulation based on ball milling.

[0027] The stirring speed of the first-stage stirring treatment in this embodiment is 550-600 r / min, and the stirring is for 15 minutes; the stirring speed of the second-stage stirring treatment is 300-350 r / min, and the stirring is for 40-50 minutes.

[0028] The present embodiment provides a method for preparing a nano-additive material composite powder and its application in laser melting additive manufacturing.

[0029] Example 1 A method for preparing a nano-additive material composite powder of this embodiment includes the following steps: Step 1: Weigh the raw materials by weight: 45 parts of Al powder, 5 parts of Ni powder, 8 parts of nano-enhanced modified particles and 10 parts of ball preparation based on ball milling; Step 2: feeding the above raw materials into a ball mill for wet ball milling, with a ball milling speed of 1000r / min and ball milling for 1h. After the ball milling is completed, filtering and drying are performed until the moisture content is less than 5%; Step 3: preparing additive material by selective laser melting the product of step 2; Step 4: The additive material is subjected to thermal improvement treatment, and finally ball-milled into powder, and then passed through 200 meshes to obtain nano-additive material composite powder.

[0030] The energy density of the selective laser melting in this embodiment is 90 J / m, and the scanning speed is 1000 mm / s; and the selective laser melting method adopts plane line-by-line scanning and layer-by-layer scanning, and the energy density of each layer fluctuates by 20 J / m; The specific steps of thermal improvement treatment are: first increase the temperature to 350°C at a rate of 2°C / min, keep warm for 2 hours, then reduce the temperature to 220°C at a rate of 3°C / min, keep warm for 1 hour, and finally air cool to room temperature.

[0031] The preparation method of the nano-enhanced modified particles of this embodiment is: S01: Stir TiC in a sufficient amount of acid solution, then wash, filter and dry. Preheat the dried TiC powder at 55°C for 1h to obtain preheated TiC powder. S02: adding 3 parts by weight of cerium oxide and 1 part by weight of silicon nitride to 5 parts by weight of 5% urea solution and mixing them thoroughly to obtain a first conditioning solution; 3 parts by weight of magnesium fluoride, 1 part by weight of silane coupling agent KH550 and 4 parts by weight of sodium dodecyl sulfate solution are mixed to obtain a second conditioning solution; S03: the first conditioning liquid and the second conditioning liquid are stirred and mixed in a weight ratio of 3:5 to obtain a cerium-doped conditioning liquid; S04: subjecting the preheated TiC powder and the cerium-doped conditioning liquid to ultrasonic modification in a weight ratio of 4:7, and after the ultrasonic modification is completed, filtering and drying are performed to obtain a modified TiC agent; The conditioned TiC agent and the reinforcing agent were mixed and ball-milled in a weight ratio of 5:3 at a ball-milling speed of 1500 r / min for 2 h. After the ball-milling was completed, the particles were filtered and dried to obtain nano-enhanced modified particles.

[0032] The acid solution in this embodiment is a sulfuric acid solution with a mass fraction of 5%; the mass fraction of the sodium dodecyl sulfate solution is 3%.

[0033] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 350W, and the ultrasonic treatment is carried out for 20 minutes.

[0034] The preparation method of the enhancer of this embodiment is: The boron oxide, sodium silicate solution and nano silica sol were mixed and ball-milled in a weight ratio of 3:7:2, with a ball-milling speed of 1000 r / min for 2 h to obtain a compounding agent; 4 parts by weight of the compounding agent, 1 part by weight of zirconium oxide and 5 parts by weight of dopamine hydrochloride solution were fully mixed to obtain a reinforcing agent.

[0035] The mass fraction of the sodium silicate solution in this embodiment is 5%; the mass fraction of the dopamine hydrochloride solution is 2%.

[0036] The preparation method of the ball preparation based on ball milling of this embodiment is: S11: preparing a 3% by mass chitosan solution and a 2% by mass sodium alginate solution; S12: 3 parts of Ta powder are added to 5 parts of sodium alginate solution for primary stirring treatment, and then 2 parts of chitosan solution and 1 part of sodium carboxymethyl cellulose are added for secondary stirring treatment to obtain a ball formulation based on ball milling.

[0037] The stirring speed of the first-stage stirring treatment in this embodiment is 550 r / min, and the stirring is for 15 min; the stirring speed of the second-stage stirring treatment is 300 r / min, and the stirring is for 40 min.

[0038] The present embodiment provides a method for preparing a nano-additive material composite powder and its application in laser melting additive manufacturing.

[0039] Example 2 A method for preparing a nano-additive material composite powder of this embodiment includes the following steps: Step 1: Weigh the raw materials by weight: 50 parts of Al powder, 7 parts of Ni powder, 12 parts of nano-enhanced modified particles and 15 parts of ball preparation based on ball milling; Step 2: feeding the above raw materials into a ball mill for wet ball milling, with a ball milling speed of 1000r / min and ball milling for 1h. After the ball milling is completed, filtering and drying are performed until the moisture content is less than 5%; Step 3: preparing additive material by selective laser melting the product of step 2; Step 4: The additive material is subjected to thermal improvement treatment, and finally ball-milled into powder, and then passed through 200 meshes to obtain nano-additive material composite powder.

[0040] The energy density of the selective laser melting in this embodiment is 90 J / m, and the scanning speed is 1000 mm / s; and the selective laser melting method adopts plane line-by-line scanning and layer-by-layer scanning, and the energy density of each layer fluctuates by 20 J / m; The specific steps of thermal improvement treatment are: first increase the temperature to 350°C at a rate of 5°C / min, keep warm for 2 hours, then reduce the temperature to 220°C at a rate of 3°C / min, keep warm for 1 hour, and finally air cool to room temperature.

[0041] The preparation method of the nano-enhanced modified particles of this embodiment is: S01: Stir TiC in a sufficient amount of acid solution, then wash, filter and dry. Preheat the dried TiC powder at 60°C for 1h to obtain preheated TiC powder. S02: adding 5 parts by weight of cerium oxide and 3 parts by weight of silicon nitride to 8 parts by weight of 5% urea solution and mixing them thoroughly to obtain a first conditioning solution; 5 parts by weight of magnesium fluoride, 3 parts by weight of silane coupling agent KH550 and 7 parts by weight of sodium dodecyl sulfate solution are mixed to obtain a second conditioning solution; S03: the first conditioning liquid and the second conditioning liquid are stirred and mixed in a weight ratio of 3:5 to obtain a cerium-doped conditioning liquid; S04: subjecting the preheated TiC powder and the cerium-doped conditioning liquid to ultrasonic modification in a weight ratio of 4:7, and after the ultrasonic modification is completed, filtering and drying are performed to obtain a modified TiC agent; The conditioned TiC agent and the reinforcing agent were mixed and ball-milled in a weight ratio of 5:3 at a ball-milling speed of 1500 r / min for 2 h. After the ball-milling was completed, the particles were filtered and dried to obtain nano-enhanced modified particles.

[0042] The acid solution in this embodiment is a sulfuric acid solution with a mass fraction of 5%; the mass fraction of the sodium dodecyl sulfate solution is 5%.

[0043] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 400W, and the ultrasonic treatment is performed for 20 minutes.

[0044] The preparation method of the enhancer of this embodiment is: The boron oxide, sodium silicate solution and nano silica sol were mixed and ball-milled in a weight ratio of 5:11:2, with a ball-milling speed of 1000 r / min for 2 h to obtain a compounding agent; 7 parts by weight of a compounding agent, 2 parts by weight of zirconium oxide and 8 parts by weight of a dopamine hydrochloride solution are fully mixed to obtain a reinforcing agent.

[0045] The mass fraction of the sodium silicate solution in this embodiment is 8%; the mass fraction of the dopamine hydrochloride solution is 5%.

[0046] The preparation method of the ball preparation based on ball milling of this embodiment is: S11: preparing a 5% by mass chitosan solution and a 5% by mass sodium alginate solution; S12: 5 parts of Ta powder are added to 8 parts of sodium alginate solution for primary stirring treatment, and then 3 parts of chitosan solution and 2 parts of sodium carboxymethyl cellulose are added for secondary stirring treatment to obtain a ball formulation based on ball milling.

[0047] The stirring speed of the first-stage stirring treatment in this embodiment is 600 r / min, and the stirring is for 15 min; the stirring speed of the second-stage stirring treatment is 350 r / min, and the stirring is for 50 min.

[0048] The present embodiment provides a method for preparing a nano-additive material composite powder and its application in laser melting additive manufacturing.

[0049] Example 3 A method for preparing a nano-additive material composite powder of this embodiment includes the following steps: Step 1: Weigh the raw materials by weight: 47.5 parts of Al powder, 6 parts of Ni powder, 10 parts of nano-enhanced modified particles and 12.5 parts of ball preparation based on ball milling; Step 2: feeding the above raw materials into a ball mill for wet ball milling, with a ball milling speed of 1000r / min and ball milling for 1h. After the ball milling is completed, filtering and drying are performed until the moisture content is less than 5%; Step 3: preparing additive material by selective laser melting the product of step 2; Step 4: The additive material is subjected to thermal improvement treatment, and finally ball-milled into powder, and then passed through 200 meshes to obtain nano-additive material composite powder.

[0050] The energy density of the selective laser melting in this embodiment is 90 J / m, and the scanning speed is 1000 mm / s; and the selective laser melting method adopts plane line-by-line scanning and layer-by-layer scanning, and the energy density of each layer fluctuates by 20 J / m; The specific steps of thermal improvement treatment are: first increase the temperature to 350°C at a rate of 2-5°C / min, keep warm for 2 hours, then reduce the temperature to 220°C at a rate of 3°C / min, keep warm for 1 hour, and finally air cool to room temperature.

[0051] The preparation method of the nano-enhanced modified particles of this embodiment is: S01: Stir TiC in a sufficient amount of acid solution, then wash, filter and dry. Preheat the dried TiC powder at 57.5°C for 1h to obtain preheated TiC powder. S02: adding 4 parts by weight of cerium oxide and 2 parts by weight of silicon nitride to 6.5 parts by weight of 5% urea solution and mixing them thoroughly to obtain a first conditioning solution; 4 parts by weight of magnesium fluoride, 2 parts by weight of silane coupling agent KH550 and 5.5 parts by weight of sodium dodecyl sulfate solution are mixed to obtain a second conditioning solution; S03: the first conditioning liquid and the second conditioning liquid are stirred and mixed in a weight ratio of 3:5 to obtain a cerium-doped conditioning liquid; S04: subjecting the preheated TiC powder and the cerium-doped conditioning liquid to ultrasonic modification in a weight ratio of 4:7, and after the ultrasonic modification is completed, filtering and drying are performed to obtain a modified TiC agent; The conditioned TiC agent and the reinforcing agent were mixed and ball-milled in a weight ratio of 5:3 at a ball-milling speed of 1500 r / min for 2 h. After the ball-milling was completed, the particles were filtered and dried to obtain nano-enhanced modified particles.

[0052] The acid solution in this embodiment is a sulfuric acid solution with a mass fraction of 5%; the mass fraction of the sodium dodecyl sulfate solution is 4%.

[0053] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 375W, and the ultrasonic treatment is carried out for 20 minutes.

[0054] The preparation method of the enhancer of this embodiment is: The boron oxide, sodium silicate solution and nano silica sol were mixed and ball-milled in a weight ratio of 4:9:2, with a ball-milling speed of 1000 r / min for 2 h to obtain a compounding agent; 5.5 parts by weight of the compounding agent, 1.5 parts by weight of zirconium oxide and 6.5 parts by weight of dopamine hydrochloride solution were fully mixed to obtain a reinforcing agent.

[0055] The mass fraction of the sodium silicate solution in this embodiment is 6.5%; the mass fraction of the dopamine hydrochloride solution is 3.5%.

[0056] The preparation method of the ball preparation based on ball milling of this embodiment is: S11: preparing a 4% by mass chitosan solution and a 3.5% by mass sodium alginate solution; S12: 4 parts of Ta powder are stirred in 6.5 parts of sodium alginate solution, and then 2.5 parts of chitosan solution and 1.5 parts of sodium carboxymethyl cellulose are added, and stirred in the second stage to obtain a ball formulation based on ball milling.

[0057] The stirring speed of the first-stage stirring treatment in this embodiment is 570 r / min, and the stirring is for 15 min; the stirring speed of the second-stage stirring treatment is 325 r / min, and the stirring is for 45 min.

[0058] The present embodiment provides a method for preparing a nano-additive material composite powder and its application in laser melting additive manufacturing.

[0059] Comparative Example 1 The difference from Example 3 is that no nano-enhanced modified particles are added.

[0060] Comparative Example 2 The difference from Example 3 is that no modified TiC agent is added in the preparation of the nano-enhanced modified particles.

[0061] Comparative Example 3 The difference from Example 3 is that no preheated TiC powder is added in the preparation of the adjusted TiC agent.

[0062] Comparative Example 4 The difference from Example 3 is that no cerium-doped conditioning liquid is added in the preparation of the conditioned TiC agent.

[0063] Comparative Example 5 The difference from Example 3 is that the first conditioning liquid is not added in the preparation of the cerium-doped conditioning liquid.

[0064] Comparative Example 6 The difference from Example 3 is that no cerium oxide or silicon nitride is added to the first conditioning solution.

[0065] Comparative Example 7 The difference from Example 3 is that no second conditioning liquid is added in the preparation of the cerium-doped conditioning liquid.

[0066] Comparative Example 8 The difference from Example 3 is that magnesium fluoride and silane coupling agent KH550 are not added to the second conditioning solution.

[0067] Comparative Example 9 The difference from Example 3 is that no reinforcing agent is added in the preparation of the nano-enhanced modified particles.

[0068] Comparative Example 10 The difference from Example 3 is that no ball preparation based on ball milling is added.

[0069] Comparative Example 11 The difference from Example 3 is that Ta powder and chitosan solution were not added in the preparation of the ball formulation based on ball milling.

[0070] The products of Examples 1-3 and Comparative Examples 1-11 were tested for strength, wear resistance (friction and wear test was carried out using a friction and wear tester, the test conditions were: loading load 10 kg, wear time 30 min, wear frequency 10 HAZ, and the grinding material was GCr15 steel ball (55 HRC)) and elongation performance under normal conditions; 50 J / cm Impact toughness is impacted for 1 hour, and at the same time, the product is heated to 150℃, kept warm for 1 hour, and then cooled with 5℃ water for 2 hours, then cooled to -20℃, kept warm for 1 hour, and then heated with 50℃ water for 2 hours. The above is one cycle, and the cycle is repeated 10 times to test the product's impact resistance and thermal stability. The performance test is shown in Table 1, which is a performance test table of strength, wear resistance and elongation; Table 1:

[0071] It is concluded from Examples 1-3 and Comparative Examples 1-11 that The product of Example 3 of the present invention has excellent tensile strength under normal conditions, and also has excellent wear resistance and elongation performance. The strength, wear resistance and elongation performance of the product can be improved in a coordinated manner. The product still has excellent performance under the conditions of impact resistance and thermal shock resistance, and has strong performance stability. From Comparative Examples 1-11 and Example 3, it can be seen that the performance of the product deteriorated significantly when the present invention did not add the nano-enhanced modified particles and did not add one of the ball additives based on ball milling. The performance effect of the product was significant when the two were coordinated and synergistic. The performance of the products showed a trend of deterioration to varying degrees when no conditioned TiC agent was added to the preparation of the nano-reinforced modified particles, no preheated TiC powder was added to the preparation of the conditioned TiC agent, no cerium-doped conditioning liquid was added to the preparation of the cerium-doped conditioning liquid, no first conditioning liquid was added to the preparation of the cerium-doped conditioning liquid, no cerium oxide and silicon nitride were added to the first conditioning liquid, no second conditioning liquid was added to the preparation of the cerium-doped conditioning liquid, and no magnesium fluoride and silane coupling agent KH550 were added to the second conditioning liquid; and the performance of the products showed a relatively obvious trend of deterioration when no reinforcing agent was added to the preparation of the nano-reinforced modified particles; The cerium-doped conditioning liquid prepared by combining the first conditioning liquid and the second conditioning liquid obtained by the specific method of the present invention, and the conditioned TiC agent obtained by combining with the specific preheated TiC powder, have the most significant product performance effects. At the same time, the performance effects of the products made by combining the conditioned TiC agent obtained by the method of the present invention and the nano-reinforced modified particles are the most significant. At the same time, Ta powder and chitosan solution are not added in the preparation of the ball preparation based on ball milling, and the performance of the product also shows a relatively obvious trend of deterioration.

[0072] Since the enhancer has a significant impact on the performance of the product, further research is needed: The preparation method of the enhancer is: The boron oxide, sodium silicate solution and nano silica sol were mixed and ball-milled in a weight ratio of 4:9:2, with a ball-milling speed of 1000 r / min for 2 h to obtain a compounding agent; 5.5 parts by weight of the compounding agent, 1.5 parts by weight of zirconium oxide and 6.5 parts by weight of dopamine hydrochloride solution were fully mixed to obtain a reinforcing agent.

[0073] The mass fraction of the sodium silicate solution in this embodiment is 6.5%; the mass fraction of the dopamine hydrochloride solution is 3.5%.

[0074] Experimental Example 1 The same as Example 3, except that zirconium oxide was not added in the preparation of the reinforcing agent.

[0075] Experimental Example 2 The same as Example 3, except that no dopamine hydrochloride solution was added in the preparation of the enhancer.

[0076] Experimental Example 3 The same as Example 3, except that boron oxide was not added in the preparation of the compounding agent.

[0077] Experimental Example 4 The same as Example 3, the only difference is that the sodium silicate solution and nano silica sol are not added in the preparation of the compounding agent.

[0078] Experimental Example 5 The same as Example 3, except that the mass fraction of the sodium silicate solution is 4%; the mass fraction of the dopamine hydrochloride solution is 6%.

[0079] The performance tests of the products of Experimental Examples 1-5 are shown in Table 2 below. Table 2 is a test table showing the effect of the preparation of the enhancer on the performance of the product; Table 2:

[0080] It can be seen from Experimental Examples 1-5 that when zirconium oxide is not added in the preparation of the reinforcing agent, the performance of the product deteriorates significantly. At the same time, when boron oxide is not added in the preparation of the compounding agent, the performance effect of the product is poor. When dopamine hydrochloride solution is not added in the preparation of the reinforcing agent, sodium silicate solution and nano-silica sol are not added in the preparation of the compounding agent, the performance of the product has a tendency to deteriorate to varying degrees. The reinforcing agent obtained by using a specific compounding agent in combination with specific raw materials has the most significant performance effect of the product. The mass fraction of the sodium silicate solution is 4%; the mass fraction of the dopamine hydrochloride solution is 6%, and the performance of the product also shows a tendency to deteriorate. Only in the specific mass fraction range of the present invention, the performance effect of the product is most obvious.

Claims

1. A method for preparing a nano-additive material composite powder, characterized in that: The following steps are involved: Step 1: Weigh the raw materials by weight: 45-50 parts of Al powder, 5-7 parts of Ni powder, 8-12 parts of nano-enhanced modified particles and 10-15 parts of ball preparation based on ball milling; Step 2: feeding the above raw materials into a ball mill for wet ball milling, with a ball milling speed of 1000r / min and ball milling for 1h. After the ball milling is completed, filtering and drying are performed until the moisture content is less than 5%; Step 3: preparing additive material by selective laser melting the product of step 2; Step 4: The additive material is subjected to thermal improvement treatment, and finally ball-milled into powder, and then passed through 200 meshes to obtain nano-additive material composite powder.

2. The method for preparing a nano-additive material composite powder according to claim 1, characterized in that: The energy density of selective laser melting is 90 J / m, and the scanning speed is 1000 mm / s; and the selective laser melting method adopts plane line-by-line scanning and layer-by-layer scanning, and the energy density of each layer fluctuates by 20 J / m.

3. The method for preparing a nano-additive material composite powder according to claim 1, characterized in that: The specific steps of the thermal improvement treatment are: first increase the temperature to 350°C at a rate of 2-5°C / min, keep it warm for 2h, then reduce the temperature to 220°C at a rate of 3°C / min, keep it warm for 1h, and finally air cool to room temperature.

4. The method for preparing a nano-additive material composite powder according to claim 1, characterized in that: The preparation method of nano-enhanced modified particles is: S01: Stir TiC in a sufficient amount of acid solution, then wash, filter and dry. Preheat the dried TiC powder at 55-60°C for 1h to obtain preheated TiC powder. S02: adding 3-5 parts by weight of cerium oxide and 1-3 parts by weight of silicon nitride to 5-8 parts by weight of 5% urea solution and mixing them thoroughly to obtain a first conditioning solution; 3-5 parts by weight of magnesium fluoride, 1-3 parts by weight of silane coupling agent KH550 and 4-7 parts by weight of sodium dodecyl sulfate solution are mixed to obtain a second conditioning solution; S03: the first conditioning liquid and the second conditioning liquid are stirred and mixed in a weight ratio of 3:5 to obtain a cerium-doped conditioning liquid; S04: subjecting the preheated TiC powder and the cerium-doped conditioning liquid to ultrasonic modification in a weight ratio of 4:7, and after the ultrasonic modification is completed, filtering and drying are performed to obtain a modified TiC agent; The conditioned TiC agent and reinforcing agent were mixed and ball-milled in a weight ratio of 5:3 at a ball-milling speed of 1500 r / min for 2 h. After the ball-milling was completed, the mixture was filtered and dried to obtain nano-enhanced modified particles.

5. The method for preparing a nano-additive material composite powder according to claim 4, characterized in that: The acid solution is a sulfuric acid solution with a mass fraction of 5%; the mass fraction of the sodium dodecyl sulfate solution is 3-5%.

6. The method for preparing a nano-additive material composite powder according to claim 4, characterized in that: The ultrasonic power of the ultrasonic modification treatment is 350-400W, and the ultrasonic treatment lasts for 20 minutes.

7. The method for preparing a nano-additive material composite powder according to claim 4, characterized in that: The preparation method of the enhancer is: The boron oxide, sodium silicate solution and nano-silica sol are mixed and ball-milled in a weight ratio of (3-5): (7-11): 2, with a ball-milling speed of 1000 r / min for 2 hours, and the ball-milling is completed to obtain a compounding agent; 4-7 parts by weight of the compounding agent, 1-2 parts by weight of zirconium oxide and 5-8 parts by weight of dopamine hydrochloride solution are fully mixed to obtain a reinforcing agent.

8. The method for preparing a nano-additive material composite powder according to claim 7, characterized in that: The mass fraction of the sodium silicate solution is 5-8%; the mass fraction of the dopamine hydrochloride solution is 2-5%.

9. The method for preparing a nano-additive material composite powder according to claim 1, characterized in that: The preparation method of the ball preparation based on ball milling is: S11: preparing a chitosan solution with a mass fraction of 3-5% and a sodium alginate solution with a mass fraction of 2-5%; S12: 3-5 parts of Ta powder are stirred in 5-8 parts of sodium alginate solution, and then 2-3 parts of chitosan solution and 1-2 parts of sodium carboxymethyl cellulose are added, and stirred in the second stage to obtain a ball formulation based on ball milling; The stirring speed of the first-stage stirring treatment is 550-600 r / min, and the stirring is for 15 minutes; the stirring speed of the second-stage stirring treatment is 300-350 r / min, and the stirring is for 40-50 minutes.

10. Application of the method for preparing the nano-additive material composite powder according to any one of claims 1 to 9 in laser melting additive manufacturing.

Citation Information

Patent Citations

  • High-performance two-phase hybrid reinforced aluminum-based composite material and preparation method thereof

    CN114350998A

  • Method for enhancing performance of additive manufactured nickel-based superalloy through carbide, nickel-based superalloy powder and application of nickel-based superalloy powder

    CN114480901A

  • High-density tungsten alloy and preparation method thereof

    CN117004855A

  • TiC particle reinforced aluminum alloy powder for metal 3D printing and preparation method of TiC particle reinforced aluminum alloy powder

    CN119351829A

  • Al-Ce-Mg aluminum alloy for metal 3D printing and preparation method of Al-Ce-Mg aluminum alloy

    CN119351830A